Direito fundamental à jurisdição efetiva e as medidas executivas atípicas na execução de obrigação de pagar quantia certa: o alcance e os limites da aplicação do inciso IV, do artigo 139, do Código de Processo Civil - Zaffari, Pedro Alexandre Bergman (2023)
This Dissertation focuses on New Paradigms of Law, inserted in the line of research Constitutional Jurisdiction and Democracy and seeks to analyze the possibility, the limits and scope of the use of atypical executive measures as a way of coercing the executed to fulfill the pecuniary obligation, based on the fundamental right to access to justice, effective judicial protection and a reasonable duration of the process. More specifically, it intends to examine the possibility of imposing a fine monetary penalty, suspension of the National Driving License (CNH) and seizure of the passport of the debtor, as a way of psychologically putting pressure on him and getting him to comply with the obligation to pay amount. Already under the aegis of the Federal Constitution of 1988, after the reform of the Civil Procedure Code of 2015 and the advent of its article 139, item IV, the judge was authorized to application of any inductive, coercive, mandatory, subrogatory and atypical measures that it deems necessary for the effective fulfillment of the obligation, including those that have subject to the delivery of a sum of money. Given the application of techniques not typified by Code of Civil Procedure and endowed with the judge's discretion, doctrine and jurisprudence began to diverge regarding the limits for the application of atypical executive means, understanding, sometimes, that such measures are excessive and violate fundamental rights of the debtor. While another portion understands that it is possible to apply it in the search for guardianship effective jurisdiction and the dignity of Justice, being just another means to achieve good of life protected by the creditor and not giving rise to a violation of the fundamental rights of the debtor in the process. In the end, the results found demonstrated the unfeasibility of applying daily fine in the obligations to pay a certain amount, however, the possibility of suspending the CNH and the seizure of the debtor's passport, as long as some minimum requirements are met, verified based on the specific case.